Legal Protection and Commercialization Opportunities for Copyright of Architectural Works - Yuswar, Cheryl Patriana; Adrian, Rio (Talenta Publisher, 2025)
Based on Law Number 28 of 2014 concerning Copyright (UUHC), architectural works are protected creations and are entitled to moral and economic rights. This protection covers the physical building, plans, technical drawings, and building models. Depending on involvement in the creation process, the architect, service user, or both can have the creator status. However, architectural copyright protection is still not optimal, as marked by the low number of copyright registrations for architectural works. Factors such as minimal UUHC outreach, communal culture, and lack of clear rules regarding copyright infringement contribute to this situation. In addition to protection, this article discusses opportunities for commercializing architectural works through licensing. Licensing agreements, exclusive and non-exclusive, can be a way for Architects to maximize their economic rights by adapting architectural works to other media, such as books, fashion, or toys. This aims to encourage innovation and provide economic benefits for creators.